Analisis Etika Pemasaran Islam Pada Bank Syariah (Studi Pada BPRS Metro Madani Kc. Tulang Bawang Barat - Baidhowi, Muhammad Mujib; Hotman, Hotman; Eriyanti, Siti Amalia (Jeksyah: Islamic Economics Journal, 2021)
This research aims to see the influence of Islamic marketing ethics on customer decisions using Islamic banking services applied in BPRS Metro Madani KC Tulang Bawang Barat. This research uses quantitative methods. The technical analysis used is multiple linear regression. The data used are primary data obtained through the dissemination of spaciousness questionnaires, with the number of respondents as many as 66 samples. The population in this study is a customer at BPRS Metro Madani KC. Tulang Bawang Barat. The results of the study of the four variables used resulted in three variables that have a significant influence on customer decisions in using Islamic banking products, namely honesty variables, responsibility variables, and wisdom variables. While the balance variable produces an insignificant influence on the results of calculations. However, overall marketing ethics that have been presented have a positive impact on customers to influence customer decisions in using Islamic banking products at BPRS Metro Madani KC. Tulang Bawang Barat.